RELATIONSHIP BETWEEN KERONCONG MUSIC THERAPHY WITH DEPRESSION OF THE ELDERLY LEVEL AT PANTI WREDHA BUDHI DHARMA YOGYAKARTA - Pramesti, Despita (Jurnal Kesehatan Samodra Ilmu (JKSI), 2019)
Background : The elderly society assumed as society which is risk health problem, includes mental health problems that is depression disorder. There are several treatments that can reduce depression, one of which is with music. Services are recreational activities that are developed at Panti Wredha Budhi Dharma is keroncong music therapy activities. The Aim : To Find out the relationship keroncong music therapy and depression of the elderly level at Panti Wredha Budhi Dharma. Methods : This research uses the correlational analytic survey with cross sectional approach. The study population amounted to 52 elderly people, there are 30 samples elderly people by sampling methods using purposive sampling method.The research instrument is the questionnaire, the method of data analysis uses Kendall 's tau test. Results : There is a relationship between the level of keroncong music therapy of depression in the elderly at Budhi Dharma. It is indicated of Kendall - Tau correlation values ( τ ) of 0.699 with p value = 0.000 Conclusion : There is a relationship keroncong music therapy and depression of the elderly level at Panti Wredha Budhi Dharma.